PEMBELAJARAN PAI DI SEKOLAH DASAR BERBASIS MODE KERTAS PLATFORM QUIZIZZ - Yusuf, Achmad; Faqih, Moch. Abdulloh; Makhzuniyah, Minhah (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
This research explores the use of the Quizizz Application Paper Mode as a strategy to increase enthusiasm for learning Islamic Religious Education (PAI) in class V students at SDN GERBO II. The main focus of this research is Paper Mode Quizizz, a platform that attracts students' interest and has the potential to increase their focus. The main aim of this research is to raise students' enthusiasm for learning through the application of innovative learning methods. The method used in this research is descriptive qualitative, where this research aims to provide an overview of the condition of students' enthusiasm for learning by focusing on indicators of interest and concentration in class V students at SDN GERBO II. Various data collection instruments were used, including observation sheets, student questionnaires, and interview guides. Data obtained from the results of student questionnaires and interviews were then analyzed to gain an in-depth understanding of the impact of using the Quizizz Application on students' enthusiasm for learning. The research results show that implementing the Quizizz application as an effective learning tool not only increases student enthusiasm in general, but also specifically has a positive impact on students who were previously less active. These findings underline the great potential of innovative approaches in motivating students and improving the quality of PAI learning at SDN GERBO II